(untitled) (Historia, 2021)
The study of ancient history, no less than of modern history, hasbeen plagued by men of undoubted high intent who have had an unflinchingloyalty to a preconception. Thus, for instance, Toynbee in making theGraeco-Roman ’civilization’ the key to the understanding of twenty othercivilizations did violence to the facts about Greek arid Roman politicaldevelopments. The influence of preconceptions is most noticeable instudies of 4th Century and Hellenistic era history: for men like Beloch,the unifying strength of Prussia and Savoy was honourable and its successinevitable, hence their conclusion that the opposition of Demosthenes andhis like to Philip and his son Alexander the Great of Macedon was bothfutile and inane. Other scholars fell under the spell of the humanitarianinterests of 19th century British scholarship, and followed Grote in depictingDemosthenes as a pillar of sanity in a decaying world, and an heroicprotagonist against the encroachments of Macedonian totalitarianism.